2013
DOI: 10.1007/s10519-013-9604-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Neurophysiological Correlates of the Age of Onset of Alcohol Use Disorders in Adolescents and Young Adults

Abstract: Discrete time survival analysis (DTSA) was used to assess the age-specific association of event related oscillations (EROs) and CHRM2 gene variants on the onset of regular alcohol use and alcohol dependence. The subjects were 2938 adolescents and young adults ages 12 to 25. Results showed that the CHRM2 gene variants and ERO risk factors had hazards which varied considerably with age. The bulk of the significant age-specific associations occurred in those whose age of onset was under 16. These associations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 92 publications
1
22
0
Order By: Relevance
“…Work in humans suggests that genetic contributions to alcohol abuse may be considerably stronger during adulthood compared to adolescence (van Beek et al ., 2012, Edwards et al ., 2015; also see Chorlian et al ., 2013; Guo et al ., 2015). Indeed, adolescent B6 mice voluntarily drink more ethanol than adults, an ontogenetic difference not observed in mice from the DBA/2J strain (Moore et al ., 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Work in humans suggests that genetic contributions to alcohol abuse may be considerably stronger during adulthood compared to adolescence (van Beek et al ., 2012, Edwards et al ., 2015; also see Chorlian et al ., 2013; Guo et al ., 2015). Indeed, adolescent B6 mice voluntarily drink more ethanol than adults, an ontogenetic difference not observed in mice from the DBA/2J strain (Moore et al ., 2010).…”
Section: Discussionmentioning
confidence: 96%
“…A study by Sovio et al (2009) found age (infancy compared to puberty) but no sex specific genotypic effects for a number of SNPs (Table 2 in Sovio et al (2009)) for height velocity. More peripheral instances of age variation in genotypic effect were shown in Chorlian et al (2013) where some CHRM2 SNPs were found to affect risk for the onset of alcohol dependence in adolescents and young adults only in those who became alcohol dependent under the age of 16 and in Hill et al (2013), mentioned above.…”
Section: Discussionmentioning
confidence: 96%
“…These findings are in concert with prior research that has shown higher rates of alcohol dependence in individuals who begin drinking at an early age. 33 …”
Section: Discussionmentioning
confidence: 99%